Conditioned emergence: a dissipative structures approach to transformation - MacIntosh, Robert; MacLean, Donald (Strategic Management Journal, 1999)
This paper presents a novel framework for the management of organizational transformation, defined here as a relatively rapid transition from one archetype to another. The concept of dissipative structures, from the field of complexity theory, is used to develop and explain a specific sequence of activities which underpin effective transformation. This sequence integrates selected concepts from the literatures on strategic change, organizational learning, and business processes; in so doing, it introduces a degree of prescriptiveness which differentiates it from other managerial interpretations of complexity theory. Specifically, it proposes a three-stage process: first, the organization ‘conditions’ the outcome of the transformation process by articulating and reconfiguring the rules which underpin its deep structure; second, it takes steps to move from its current equilibrium; and, finally, it moves into a period where positive and negative feedback loops become the focus of managerial attention. The paper argues that by managing at the level of deep structure in social systems, organizations can gain some influence over self-organizing processes which are typically regarded as unpredictable in the natural sciences. However, the paper further argues that this influence is limited to archetypal features and that detailed forms and behaviors are emergent properties of the system. Two illustrative case vignettes are presented to give an insight into the practical application of the model before conclusions are reached which speculate on the implications of this approach for strategy research. Copyright © 1999 John Wiley & Sons, Ltd.